Longitudinal study of medication use in caregivers of people with Alzheimer's disease – Kuopio ALSOVA study. (July 2020) - Välimäki, Tarja; Gilmartin-Thomas, Julia FM; Bell, J Simon; Selander, Tuomas; Koivisto, Anne M
Background: The longitudinal pattern of medication use among family caregivers of people with dementia is not well understood, despite the potential for medication over- or under-use. Objectives: To investigate caregiver medication use over a five-year follow-up using data obtained via self-report and from a national prescription register, and compare agreement between medication data obtained from the two sources. Methods: Medication data for 222 family caregivers of people with Alzheimer's disease were obtained via self-report and from the Finnish Social Insurance Institution. Generalised estimating equations, Kappa statistics and related samples Wilcoxon signed rank test were used to analyse medication use over time. Results: The mean number of medications used by caregivers increased from 3.4 to 4.1 (self-reported current regular medications) and 2.4 to 2.8 (reimbursed prescription medications during the past 90 days) over five years (p < 0.001). Significantly, more medications were identified via self-report (mean 3.6, SD = 3.3) than the national prescription register (mean 2.6, SD = 2.4, Z= –12.300, p < 0.001). Agreement between the two data sources was good for cardiovascular medications and anti-hypertensives (Kappa = 0.883–0.967, p < 0.001) and medications for acid-related disorders (Kappa = 0.508–0.092, p < 0.001). Agreement was moderate for analgesics (Kappa = 0.281–0.477, p < 0.001) and psychotropics (Kappa = 0.281–0.562, p < 0.002). The proportion of caregivers using five or more medications increased from 27.5% to 44.6% (self-report), and 16.7% to 27.7% (register) (p < 0.001). Conclusion: Caregivers use an increasing number of medications in the first five years of caring for persons with dementia, and self-report using a higher number of medications than data from the national prescription register suggest.